Penerapan Pembelajaran Kooperatif Dalam Perkuliahan Konseling Kelompok Pada Mahasiswa Bimbingan Konseling Fakultas Dakwah Dan Ilmu Komunikasi UIN Raden Intan Lampung - Muhammad Saifuddin; Sri Ilham Nasution (Jayapangus Press, 2020)
The results of Class Counseling student learning outcomes VI semester Counseling Guidance Department, Faculty of Da'wah and Communication Studies, UIN Raden Intan Lampung in the previous year showed the low ability of students, especially in the subject of group dynamics and stages of group counseling. This condition is caused by poor understanding and skills regarding group counseling, new material, and lecture models or approaches used by lecturers are not optimal. Therefore, the problem solved through this research is